Building a clean government in Turkey: pillars, perils, and prospects - Acar, Muhittin (Crime, law and social change, 2008)
Corruption is a serious and enduring problem in Turkey. As such, a series of sustained and synchronized actions are needed to promote integrity, and to prevent and punish corrupt practices in public life. In most recent years, subsequent cabinets have promulgated a set of laws, regulations, and measures in the name of fighting against corruption. Yet, building a clean government remains as a daunting, if not insurmountable, task for policy makers and the public at large in Turkey. The current paper begins with a brief introduction, summarizing the need for new, more effective anti-corruption policies and practices in the country. Then, it succinctly describes and assesses the main ‘pillars’ of the ‘national integrity system.’ The paper moves on to identify and evaluate the chief ‘perils,’ challenges and risks associated with efforts aiming to contribute to integrity, transparency and accountability in Turkish society. Finally, the paper discusses the ‘prospects’ for building a clean government in Turkey in the near future. Among the issues brought to the present debate are: the need for a credible commitment by the ruling elites for establishing a well-functioning integrity regime; effective coordination and collaboration among a wide range of institutional actors; developing a set of coherent principles and policies; and creating capacity to prevent, prosecute, and punish corrupt behaviors. It is also argued that building a clean government in Turkey requires a strong and sustainable coalition among the clean, the competent, and the competitive.